AB0527 S100 proteins are novel biomarkers for the efficacy of hcq treatment to skin lesion in systemic lupus erythematosus. (12th June 2018) - Wakiya, R.; Ueeda, K.; Kameda, T.; Nakashima, S.; Izumkawa, M.; Shimada, H.; Kondo, A.; Kato, M.; Miyagi, T.; Kadowaki, N.; Dobashi, H.
Abstract : Background: Systemic lupus erythematosus(SLE) is deeply associated with not only acquired immunity but also innate immunity throughout toll like receptors(TLRs) signalling. Among many TLRs, TLR7 and TLR9 were reported to be closely associated with IFN-α production which contributed the pathogenesis of SLE. On the other hand, several reports demonstrated that S100A8 and S100A9 proteins which was known as one of damage-associated molecular patterns(DAMPs), were associated with disease activity of lupus nephritis. These proteins were also shown to reflect the treatment response by immunosuppressive therapy for SLE. 1 2 However, there is no report about the effect of hydroxychloroquine(HCQ) on S100A8 and S100A9 proteins expression. Objectives: To find a new biomarker of treatment with HCQ, we focused on expression of S100A8 and S100A9 proteins in SLE. Methods: We enrolled all SLE patients treated with HCQ in the absence of additional immunosuppressive therapy more than 3 months in our institute from Jan 2016 to Dec 2017 Serum levels of S100A8 and S100A9 proteins were measured by ELISA(CircuLex ELISA Kit, MBL) at the screening, 3 months and 6 months after HCQ administration. Disease activity of SLE was measured using the SLENA-SLEDAI 2011 Cutaneous disease activity was evaluated by Cutaneous Lupus Erythematosus Disease Area and Severity Index (CLASI). Immunological activity was examined by the levels of complement (C3, C4, CH50), anti-dsDNA anti-body and counting blood cell. Results: 61 patients were enrolled in this study. HCQ was administered 48 cases with usual dose(based on ideal weight), 15 cases with low dose than usual dose (table 1). CLASI was improved by the treatment with HCQ independent of HCQ dose. However, the effect of HCQ on SLENA-SLEDAI and immunological biomarker was shown in the patients treated with usual dose HCQ, not shown in those treated with low dose HCQ. On the other hand, serum levels of S100A8 and S100A9 proteins were significantly elevated in SLE patients with renal lesion(p=0.02). These proteins were significantly decreased by the treatment with HCQ regardless of the HCQ dose(p<0.0001). The changes of serum S100A8 and S100A9 proteins during HCQ treatment(for 3 months) were significantly associated with changes of CLASI(figure 1). Conclusions: HCQ reduced the expression of serum S100A8 and S100A9 proteins, which reflected SLE disease activity especially in skin lesion. The measurement of S100A8 and S100A9 proteins is novel predictive biomarker for the efficacy of HCQ treatment on skin lesion in SLE patients. References: [1] Tyden H, et al. Pro-inflammatory S100 proteins are associated with glomerulonephritis and anti-dsDNA antibodies in systemic lupus erythematosus. Lupus2017;(26):139–149. [2] Tantivitayakul P, et al. Elevated expressions of myeloid-related proteins-8 and -14 are danger biomarkers for lupus nephritis. Lupus 2016;(25):38–45. Disclosure of Interest: None declared